An evaluation of fish early life stage tests for predicting reproductive and longer‐term toxicity from plant protection product active substances. (27th June 2014) - Wheeler, James R.; Maynard, Samuel K.; Crane, Mark
Abstract The chronic toxicity of chemicals to fish is routinely assessed by using fish early life stage (ELS) test results. Fish full life cycle (FLC) tests are generally required only when toxicity, bioaccumulation, and persistence triggers are met or when there is a suspicion of potential endocrine‐disrupting properties. This regulatory approach is based on a relationship between the results of fish ELS and FLC studies first established more than 35 yrs ago. Recently, this relationship has been challenged by some regulatory authorities, and it has been recommended that more substances should undergo FLC testing. In addition, a project proposal has been submitted to the Organisation for Economic Cooperation and Development (OECD) to develop a fish partial life cycle (PLC) test including a reproductive assessment. Both FLC and PLC tests are animal‐ and resource‐intensive and technically challenging and should therefore be undertaken only if there is clear evidence that they are necessary for coming to a regulatory decision. The present study reports on an analysis of a database of paired fish ELS and FLC endpoints for plant protection product active substances from European Union draft assessment reports and the US Environmental Protection Agency Office of Pesticide Programs Pesticide Ecotoxicity Database. Analysis of this database shows a clear relationship between ELS and FLC responses, with similar median sensitivity across substances when no‐observed‐effect concentrations (NOECs) are compared. There was also no indication that classification of a substance as a mammalian reproductive toxicant leads to more sensitive effects in fish FLC tests than in ELS tests. Indeed, the response of the ELS tests was generally more sensitive than the most sensitive reproduction NOEC from a FLC test. This analysis indicates that current testing strategies and guidelines are fit for purpose and that there is no need for fish full or partial life cycle tests for most plant protection product active substances. Environ Toxicol Chem 2014;33:1874–1878. © 2014 SETAC